(untitled) (KULT_online, 2012)
Marion Schmaus’ Psychosomatik offers a highly interesting perspective on the origins of psychosomatics as a discipline. Through discourse-analysis and a diachronic as well as synchronic comparative method, the book shows the all-encompassing and interdisciplinary character of the mind-body problem in narratives on psychosomatics from the end of the 18th to the beginning of the 20th century. Starting from concrete case-studies which are nevertheless strictly related to each other, not only does the author analyse the interactions between literary, medical and philosophical discourses, but she also reflects on her own theoretical and methodical framework, explaining the possibility and the necessity of writing a cultural history of the natural sciences.